2021
DOI: 10.1007/s11242-021-01644-9
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann Modeling of Drying of Porous Media Considering Contact Angle Hysteresis

Abstract: Drying of porous media is governed by a combination of evaporation and movement of the liquid phase within the porous structure. Contact angle hysteresis induced by surface roughness is shown to influence multi-phase flows, such as contact line motion of droplet, phase distribution during drainage and coffee ring formed after droplet drying in constant contact radius mode. However, the influence of contact angle hysteresis on liquid drying in porous media is still an unanswered question. Lattice Boltzmann mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 84 publications
1
38
0
Order By: Relevance
“…Considering the important role of wettability on drying patterns in porous media, , we analyze the implementation of an accurate contact angle. In 2007, Ding et al showed that the contact angle in complex geometries in the phase-field method can be accurately implemented based on a geometric-function scheme .…”
Section: Model Validationmentioning
confidence: 99%
“…Considering the important role of wettability on drying patterns in porous media, , we analyze the implementation of an accurate contact angle. In 2007, Ding et al showed that the contact angle in complex geometries in the phase-field method can be accurately implemented based on a geometric-function scheme .…”
Section: Model Validationmentioning
confidence: 99%
“…This should impact the fluidfluid surface area, which in turn will have impact on the mass transfer process in the interfacial region. A possibility to explore this issue could be to rely on some direct numerical simulations [44,45] on microstructure digital images using the results of the present article as guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of sub-resolution processes, e.g. contact angle hysteresis on rough surfaces, 23,24 is an ongoing challenge for coarse-grain-like models. Theoretical and experimental works on hysteresis and wetting of rough surfaces often discuss the superposition of different effects, e.g.…”
Section: Introductionmentioning
confidence: 99%